2019
DOI: 10.1007/978-3-030-24781-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Traditional Usability Evaluation in End-User Development

Abstract: End-user development (EUD) research has yielded a variety of novel environments and techniques, often accompanied by lab-based usability studies that test their effectiveness in the completion of representative real-world tasks. While lab studies play an important role in resolving frustrations and demonstrating the potential of novel tools, they are insufficient to accurately determine the acceptance of a technology in its intended context of use, which is highly dependent on the diverse and dynamic requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our previous work described Jeeves in relation to EUD adoption requirements for psychology researchers [21], as well as how usability issues in a lab study of Jeeves were almost entirely separate to real-world usability challenges identified in case studies [22]. In this work, we extend on both of these results by triangulating interview feedback with analysis of our case studies.…”
Section: The Jeeves Eud-esm Toolmentioning
confidence: 73%
See 2 more Smart Citations
“…Our previous work described Jeeves in relation to EUD adoption requirements for psychology researchers [21], as well as how usability issues in a lab study of Jeeves were almost entirely separate to real-world usability challenges identified in case studies [22]. In this work, we extend on both of these results by triangulating interview feedback with analysis of our case studies.…”
Section: The Jeeves Eud-esm Toolmentioning
confidence: 73%
“…As previously discussed, interviews alone were insufficient to determine challenges pertaining to real-world use of EUD-ESM. This section thus describes three applications of Jeeves by psychology researchers, two of which were previously discussed in prior work [22] and one currently in progress. In doing so, we highlight issues that have emerged in practical use that provide concrete suggestions for implementing requirements identified in interviews.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant because of the development of a new system that integrates an app-based cognitive task into the ESM procedure. Previous platforms have been developed to repeatedly assess affect through ESM, provide a visual environment [ 55 - 57 ], and highlight the importance of usability testing. In the case of the new ESM system used in our studies, the results on usability showed a very high level of learnability (ie, over the 90th percentile of the SUS), which reflects the ease of use and acceptability by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…This evaluation was done using the cognitive dimensions of notations framework [21]. Likewise, Rough and Quigley [126] present the challenges of traditional usability evaluations. Almjally et al [4] present an empirical study that compares the usage of a block-based language using Tangible User Interfaces (TUIs) and Graphical User Interfaces (GUIs).…”
Section: Category 3 Human Computer Interaction (Hci)mentioning
confidence: 99%